Evaluation of the effect of sesame (Sesamum Indicum L.) protein isolates on the bromatological, textural, and microstructural properties of fresh cheese - Diofanor Acevedo-Correa; Jhon Rodriguez-Meza; Carmen Molinares-Brito; Piedad Montero-Castillo; Hader Alcázar-Orozco (Applied Food Research)
In cheese making, protein loss during the draining stage and variation in textural characteristics during storage is a major problem, making vegetable proteins a viable alternative. This research focused on extracting sesame protein for use in producing fresh cheese. Different concentrations (0, 2, 4, and 8 %) of sesame protein isolate (SPI) were used to study its effect on the bromatological, textural, microstructural, and sensory characteristics of the fresh cheese; physicochemical parameters such as pH, acidity and water activity (Aw) were also evaluated. The bromatological analysis revealed cheeses with high protein contents of approximately 16.29 % to 21.65 %, and an increase in moisture content up to 51.06 %. The addition of SPI at 2 % and 4 % improved the hardness, chewiness, and cohesiveness of the cheeses; however, the addition of protein isolate at 8 % deteriorated the texture, exhibiting a reduction in the elasticity parameter. According to the sensory evaluation, sample T2 (2 % SPI), showed the best attributes very similar to T1 (0 % SPI), while higher percentages of incorporation were not acceptable in parameters such as flavor and color. Finally, this research highlights the benefits of incorporating sesame protein isolate into the quality attributes of the fresh product and adding value to this crop in the region.